Behavioral Intentions Toward Cryptocurrency Transactions: Exploring Through Snowball Sampling Among Users - Bhattarai, Bhim Prasad (Journal of Business and Management, 2025)
Background: Cryptocurrency is a digital decentralized currency that enables peer-to-peer transactions without the involvement of intermediaries, using blockchain technology to ensure security and transparency. These emotions can help understand when and what behavioral intentions toward cryptocurrency adoption are necessary. These insights contribute to the growing literature on fintech adoption in emerging economies and provide valuable guidance for policymakers and investors formulating cryptocurrency regulations in Nepal. Objectives: It aims to investigate the influence of perceived usefulness, perceived ease of use, trust, and perceived risk constructs attached to an individual’s intention to be involved in cryptocurrency transactions. It finally aims to study the relationships among these variables and their effect on cryptocurrency adoption in the Nepal context. Methods: The study uses a quantitative descriptive design and snowball sampling alone to extract information from cryptocurrency users in Nepal. A structured online questionnaire was used to gather 272 responses and analyzed using correlation and regression to investigate the significance of the proposed hypotheses. Results: Findings show that perceived usefulness, ease, or trust significantly and positively influence behavioral intention toward cryptocurrency adoption, while perceived risk harms adoption because users worry about market volatility, regulatory uncertainty, and security threats. Despite the government’s legal restrictions, many Nepalese citizens are still involved in cryptocurrency transactions, seeing it as a source of financial benefit and investment opportunity. Conclusion: The study attests that perceived usefulness, perceived ease of use, and trust motivate behavior toward adopting cryptocurrency, while perceived risk provides a barrier. This enlightens policymakers on balanced regulatory measures that address risks while encouraging innovation in digital finance. These findings would provide valuable implications for policymakers, financial institutions, and technology developers in outlining the future of cryptocurrency regulation and adoption strategies. JEL Classification: D14, E42, G41